The Genesis of the Maastricht Treaty and Its Importance for the European Integration and Security (Politeja, 2023)
The Treaty of Maastricht was signed thirty years ago, that is, on 7 February 1992, and after its ratification entered into force on 1 November 1993. It was a quantum leap into the European integration initiated after the Second World War. It constituted a basis for the creation of the European Union (EU), becoming an accelerator of the European integration and an important element of the transatlantic system of international security. Its origin and decisions rest in such contemporary events and processes as the “Autumn of Nations,” which resulted in the fall of communism in the states of Central and Eastern Europe, German reunification on 3 October 1990, the collapse of the Soviet Union in December 1991 and the global end of the Cold War. The article is aimed at analyzing the prerequisites of the genesis of the Treaty of Maastricht and showing its significance for the integration and security of Europe after the collapse of the Yalta-Potsdam order and the end of the Cold War. The main thesis statement is that the Treaty of Maastricht would not have been signed and the European Union would not have been established without the fall of communism in the states of Central and Eastern Europe, the collapse of the Soviet Union and German reunification. Moreover, I believe that international situation after the Cold War would have been less stable without the Treaty of Maastricht and the EU, because the competition for leadership between reunited Germany and France would have intensified.